Correlation arterial stiffness and central blood pressure with obstructive sleep apnea in patients with resistant arterial hypertension. (14th October 2021) - Rekovets, O; Sirenko, Y; Krushynska, N; Torbas, O; Kushnir, S; Primak, G; Granich, V; Sidorenko, P; Polishchuk, S; Zhyvilo, I; Radchenko, G; Botsyuk, Y
Abstract:  : The aim assess correlation the arterial stiffness in patients with resistant arterial hypertension (AH) and obstructive sleep apnea (OSA) Design: 185 patients with AH were enrolled into the study. They were divided on 2 groups: OSA group – 148 patients were found to have OSA, indicated by at mean AHI of 38.1±2.5 h –1, and control group – 37 patients without OSA, mean AHI 3.02±0.25 h –1 (P<0.001). Patients of both groups were comparable on age, growth, total cholesterol level and office systolic blood pressure (SBP) and diastolic blood pressure (DBP). Results: Patients with RAH and OSA (mean apnea-hypopnea index (AHI) 36.5±2.7 event/h) in comparison with patients with RAH without OSA (mean AHI 3.4±0.2 event/h) had significantly higher body mass index (34.2±0.7 vs 31.6±0.7 kg/m 2, P<0.05), uric acid level (6.7±0.1 vs 5.6±0.4 mg/dl, P<0, 05), higher carotid-femoral pulse wave velocity (PWVcf) (12.1±0.5 vs 10.2 m/s, P<0, 05) and central systolic blood pressure (CSBP) (143.8±2.7 vs 136.2±3.4 mm Hg, P<0, 05). Patients of both groups had comparable office blood pressure (SBP 145.6±1.67 vs 138.4±3.66 mm Hg, P=0.057 and DBP 93.6+±1.18 vs 89.1±2.11 mm Hg, P=0.073), but significantly higher 24-h systolic and diastolic blood pressure. We suggest that in the study some patients with OSA had masked arterial hypertension. Daytime sleepiness in OSA patients was associated with structural remodeling of the left ventricle myocardium and more expressed arterial stiffness: ESS score was independently correlated with snoring duration (β=−0.008; P=0.021), interventricular septum thickness (β=0.023; P=0.026), LVMI (β=−0.037; P=0.039) and indexes of central pulse wave: ejection duration (ED) (β=−0.020; P<0.001) and subendocardial viability ratio (SEVR) (β=−0.224; P=0.012). Nocturnal hypoxemia in OSA patients was associated with increased aortic stiffness and higher central blood pressure: desaturation index was independently correlated with Aix (β=4.167; P=0.009), Aix75 (β=−3.929; P=0.006) and central DBP (β=0.151; P=0.004). Conclusion: In patients with RH and OSA nocturnal hypoxemia correlation with increased aortic stiffness and higher central blood pressure. Funding Acknowledgement: Type of funding sources: None.